Understanding the Impact on Healthcare Professionals of Viewing Digital Stories of Adults with Cancer: A Hermeneutic Study - Catherine M. Laing (University of Calgary, 2020)
The purpose of this study was to understand the effects on oncology healthcare providers (HCPs), both personally and professionally, of watching digital stories made by adults with cancer (past and present), and what HCPs envisioned for the uses of digital stories. Seven healthcare professionals from various disciplines volunteered for this study. This research took place in a large urban center in Western Canada and was done in the tradition of philosophical hermeneutics. A 90-minute focus group was used for data collection, where participants watched eight digital stories (batched in four groups of two stories) that had been created by individuals with cancer (past or present). Data was analyzed using an interpretive qualitative methodology. Findings revealed that watching digital stories made by adults with cancer was emotionally compelling, provided context, incited deep introspection, and may offer a protective effect with respect to HCP burnout.